Genome mapping and genomics in fishes and aquatic animals - Kocher, Thomas D. (Springer, 2017)
Mapping of animal genomes has generated huge databases and several new concepts and strategies, which are useful to elucidate origin, evolution and phylogeny. Genetic and physical maps of genomes further provide precise details on chromosomal location, function, expression and regulation of academically and economically important genes. The series "Genome Mapping and Genomics in Animals" provides comprehensive and up-to-date reviews on genomic research on a large variety of selected animal systems, contributed by leading scientists from around the world. This volume summarizes the fi.